Chemical methods for modification of proteins. Issue 25 (15th June 2020) - Reddy, Neelesh C.; Kumar, Mohan; Molla, Rajib; Rai, Vishal
Abstract : The field of protein bioconjugation draws attention from stakeholders in chemistry, biology, and medicine. This review provides an overview of the present status, challenges, and opportunities for organic chemists. Abstract : The library of chemical reactions for C–C and C–heteroatom bond formation is exceptional. The understanding of reactivity and diverse aspects of selectivity facilitates the functional group transformation of high complexity. However, the same is not valid for proteins as an organic substrate. Gratifyingly, we can translate some of the pre-existing reactions for developing methods for the modification of proteins. Also, there is enormous potential to create a new knowledge domain that will be unique to the densely functionalized architecture of proteins. At the outset, we outlined a few concepts that bridge the gap between chemical reactions with small molecules and proteins. Next, we introduced the key attributes and challenges associated with the selectivity that emerges due to the presence of multiple types and copies of functional groups. The examples with nucleophilic amino acids outline the chemoselectivity-associated features. Gradually, the discussion moves toward the concepts that led to the successful realization of site-selectivity and N-terminus residue-specificity. The attributes of organic chemistry that emerge due to the multifunctional organization of the substrate are marked. The last section overviews the analysis of protein bioconjugates by mass spectrometry. Also, the review outlines the unmet needs and opportunities.